Carinus Nursing College : an historical study of nursing education and management using the general systems approach, 1947-1987 - Goodchild-Brown, Beatrix (Division of Nursing and Midwifery, 2017)
The purpose of this dissertation is to research aspects of the historical development of Nursing Education and Nursing Management at the Carinus Nursing College from 1949 to 1987; to determine and explain how the College has adapted and coped with historical change and to determine whether proposals for the future can be made. Research has been done by applying the general systems theory and by using the standard methods of historical analysis. Data has been collected by means of oral history, literature search and documentation. The variables isolated are the College as a system; the government or influential super systems; resources such as financial, personnel and students and material inputs; and throughput or processing the work in the output, which leads to the professional nurse. The models used are Bucheles' organizational system, Sharma's flow chart pattern, Mintzberg's parts of organizational systems, and power flows and as shown in Emery, Feibleman and Friends relations and rules of interaction in systems thinking. Parsons' "imperatives of maintenance of a system" as well as Alvin Toffler's "second and third wave phenomena as responses to change" were two further models that were used. By using Robert Buchele's model, the work is divided into four parts: - i) the College as a system ii) the super systems iii) the resources iv) the throughput or processing. A further design that emerged was that two eras could be distinguished, within which three historical phases: - Early, Middle and Late are developed.